The pros and cons of electronic prescribing for children. Issue 2 (18th June 2011) - Caldwell, Neil A; Power, Brian
Abstract : The move from paper to electronic prescribing (EP) and medicine administration systems has long been advocated. Initial studies in the adult setting showed a significant reduction in medication errors. However, there are additional challenges to overcome to tailor these systems to paediatrics. Building on the basic elements of EP with the development of customised paediatric clinical decision support seems to offer the most benefit in terms of error reduction and increasing clinical effectiveness. Continued research is required to optimise these systems and minimise any unintended consequences at all stages of the medication use process.